The response of flue-cured tobacco cultivar K326 to nitrogen fertilizer rate in China. (17th July 2020) - Chen, Yanjie; Ren, Ke; He, Xian; Chen, Yi; Hu, Binbin; Hu, Xiaodong; Li, Junying; Jin, Yan; Zhao, Zhengxiong; Zou, Congming
Abstract: Nitrogen is an important element for the growth of flue-cured tobacco and is closely related to its yield and quality. In order to pursue higher economic benefits, excessive fertilizer is generally applied in flue-cured tobacco production, which is unfavourable for the sustainable development of flue-cured tobacco production and for the environment. In 2016 and 2017, experiments using different nitrogen fertilizer application rates in flue-cure tobacco were conducted in Yunnan province, and the changes in agronomic, economic and chemical indices as well as in residual soil nitrogen were compared. Linear and quadratic models were used to compare the response of tobacco to nitrogen fertilizer. With increasing nitrogen fertilizer rate, the proportions of superior to medium tobacco and the average price of flue-cured tobacco leaves initially increased and then decreased, while fresh weight, dry weight and the proportion of inferior tobacco showed the opposite trend. Total sugar and reducing sugar contents decreased with increasing nitrogen fertilizer rates, while total nitrogen and nicotine contents increased. Sensory evaluation scores had the highest value when 90 kg N/ha and 120 kg N/ha were applied. Soil nitrate contents increased as nitrogen fertilizer rate increased. The quadratic model was suitable for the response of cultivar K326 to nitrogen and 90 kg N/ha could meet the needs of cultivar K326.